Spinal cord injury by a stab wound and Brown Séquard syndrome: Case report - Casallo Quiliano, Carlos (2012)
Introduction: It is unusual to observe the occurrence of Brown Séquard syndrome as a consequence of a lateral hemisection of the spinal cord caused by a stab wound. We report a case of this syndrome showing its typical presentation. Clinical Case: A male, 18-year old subject was attacked and suffered a stab wound in his right cervical area. The patient developed ipsilateral hemiparesis, an ipsilateral proprioception disturbance and a contralateral thermo-algesic disturbance. Image studies showed a laminar fracture in C6 and spinal edema in the same area. The patient underwent a C6-laminectomy. Three months after surgery, his neurological condition improved. Conclusions: It is unusual to observe the occurrence of Brown Séquard syndrome in its so-called classical or 'pure' form caused by a stab wound. The mandatory image study to perform in these cases is magnetic resonance imaging. Surgical therapy should be immediately performed only if there is evidence of a bone or metal fragment in the spinal canal, or if there is a hematoma in this area.